Peningkatan Kemampuan Menyimak Melalui Teknik Bisik Berantai - Kokomaking, Yeherlina Ohe; Usman, Misnawaty (Interference: Journal of Language, Literature, and Linguistics, 2021)
The purpose of this study was to determine the increase in listening skills trought the chain whisper technique for students in language XI class at SMA PGRI Gelekat Lewo Boru East Flores NTT. This type ofresearch is a classroom action research which consists of two cycles. The subjects in this study are for students in language XI class at SMA PGRI Gelekat Lewo Boru. The data in this study consisted of qualitative and quantitative data. Qualitative data were obtained through observation and quantitative data were obtained through the results of the listening ability test. The instrument in this study was a multiple choice and true false test. The results of data analysis showed that the listening language with the scores obtained by students in the first cycle was 80.4% and the second cycle was 87.2%. These results indicate that the application of the chain whisper technique can improve the listening ability for students in language XI class at SMA PGRI Gelekat Lewo Boru East Flores NTT.